The driving mechanism and path selection of green development in Chinese cities - Xisha, Wang; Jinye, Li (Frontiers in Environmental Science, 2023)
Green is the background color of high-quality development of Chinese cities. By constructing a theoretical model of the driving force and driving mechanism of China’s urban green development, this paper simulates the green development path of Chinese cities based on the panel data of Chinese cities from 2010 to 2020. The empirical results show that, firstly, the driven force formed by scientific and technological in novation, the action force formed by structural adjustment and the driven force formed by environmental regulation can drive Chinese cities to achieve green development. Secondly, the pressure of different paths on the ecological environment showed a gradual downward trend, the ecological environment pressure under the baseline scenario was the highest, and the ecological environment pressure driven by single factors may be lower than that driven by two factors. Finally, the comprehensive driven path formed by the combination of innovation driven, structure driven and environment a driven is a better path for China’s urban green development. Therefore, the green development of Chinese cities requires policy intervention, different cities need to formulate green development plans according to local conditions, and should consider the combination of policies. In the future, Chinese cities need to increase investment in science and technology, guide all entities to develop in the direction of resource conservation and pollution reduction, adjust the industrial structure, promote their development in the direction of cleanliness, increase environmental protection investment, standardize the development of all entities in the direction of environmental protection, and give full play to the synergy of the three major policies to achieve green development.